I am a global citizen. Or am I not? International Business Schools students and Global Citizenship unified framework & a scoping literature review of the last decade (2013-2022) - Misirlis, Nikolaos (arXiv.org, 2023)
This review examines the scientific articles of the last decade, approaching the subject through the methodology of the scoping literature review. Starting with the Boolean search global citizens AND education AND (international business OR international business school) in the ScienceDirect, Emerald, and Scopus databases, the review resulted in only scientific journal articles, strictly targeted at tertiary education ONLY of international business schools and ONLY in those articles that study global citizenship. For reasons of up-to-date knowledge, the present literature was content with the final decade. A total of 13 articles are recorded as a result of the aforementioned Boolean search from a total of 216 articles identified in the first phase of the search. The results will help the researchers to acquire the required knowledge base for their research, the academics to incorporate new methods in their teaching and the approach of their students, and the policymakers to adapt the schools curricula according to the data from the articles present in the literature review.